Serum Vitamin D and Osteoarthritis (Medical Forum Monthly, 2024)
Objective: To determine whether the serum vitamin D level is associated with increasing age in female OA patients.Study Design: Experimental and Observational Study.Place and Duration of Study: This study was conducted at the Department of Orthopaedic, Civil Hospital, Karachi from Feb. 2006 to Jan. 2008.Materials and Methods: Sixty female patients who were suffering from OA were studied. Patients were classified according to their stage of severity of OA in knee joints. Serum vitamin D was measured in serum by ELISA technique.Results: According to distribution patients of group 3 having the age between 61 – 70 years. Serum vitamin D was detected in serum. Group 3 has high serum Vitamin D levels as compared to group 1 and 2 (P < 0.5).Conclusions: The age group of between 61 years and 70 years has low vitamin D levels, indicating that old age may be one of risk factor for OA.